KAST Study: The Kiva System As a Vertebral Augmentation Treatment-A Safety and Effectiveness Trial: A Randomized, Noninferiority Trial Comparing the Kiva System With Balloon Kyphoplasty in Treatment of Osteoporotic Vertebral Compression Fractures - Tutton, Sean M; Pflugmacher, Robert; Davidian, Mark; Beall, Douglas P; Facchini, Francis R; Garfin, Steven R (Spine (Philadelphia, Pa. 1976), 2015)
The KAST (Kiva Safety and Effectiveness Trial) study was a pivotal, multicenter, randomized control trial for evaluation of safety and effectiveness in the treatment of patients with painful, osteoporotic vertebral compression fractures (VCFs). The objective was to demonstrate noninferiority of the Kiva system to balloon kyphoplasty (BK) with respect to the composite primary endpoint. Annual incidence of osteoporotic VCFs is prevalent. Optimal treatment of VCFs should address pain, function, and deformity. Kiva is a novel implant for vertebral augmentation in the treatment of VCFs. A total of 300 subjects with 1 or 2 painful osteoporotic VCFs were randomized to blindly receive Kiva (n = 153) or BK (n = 147). Subjects were followed through 12 months. The primary endpoint was a composite at 12 months defined as a reduction in fracture pain by at least 15 mm on the visual analogue scale, maintenance or improvement in function on the Oswestry Disability Index, and absence of device-related serious adverse events. Secondary endpoints included cement usage, extravasation, and adjacent level fracture. A mean improvement of 70.8 and 71.8 points in the visual analogue scale score and 38.1 and 42.2 points in the Oswestry Disability Index was noted in Kiva and BK, respectively. No device-related serious adverse events occurred. Despite significant differences in risk factors favoring the control group at baseline, the primary endpoint demonstrated noninferiority of Kiva to BK. Analysis of secondary endpoints revealed superiority with respect to cement use and site-reported extravasation and a positive trend in adjacent level fracture warranting further study. The KAST study successfully established that the Kiva system is noninferior to BK based on a composite primary endpoint assessment incorporating pain-, function-, and device-related serious adverse events for the treatment of VCFs due to osteoporosis. Kiva was shown to be noninferior to BK and revealed a positive trend in several secondary endpoints. 1.